FENOMENA BOROH DI PADANGSIDIMPUAN DALAM PERSPEKTIF FIQH MUAMALAH - Dasopang, Nur Sania (STAI Darul Qalam Tangerang, 2023)
The phenomenon that occurs in the people of North Sumatra, especially the Padangsidimpuan area is the practice of